Low-intensity focused ultrasound (LIFU)-induced acoustic droplet vaporization in phase-transition perfluoropentane nanodroplets modified by folate for ultrasound molecular imaging - Liu J (Dove Medical Press, 2017)
Jianxin Liu,1,* Tingting Shang,1,* Fengjuan Wang,1 Yang Cao,1 Lan Hao,1 JianLi Ren,1,2 Haitao Ran,1,2 Zhigang Wang,1,2 Pan Li,1,2 Zhiyu Du3 1Chongqing Key Laboratory of Ultrasound Molecular Imaging, 2Department of Ultrasound, 3Postgraduate Department, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China *These authors contributed equally to this work Abstract: The commonly used ultrasound (US) molecular probes, such as targeted microbubbles and perfluorocarbon emulsions, present a number of inherent problems including the conflict between US visualization and particle penetration. This study describes the successful fabrication of phase changeable folate-targeted perfluoropentane nanodroplets (termed FA-NDs), a novel US molecular probe for tumor molecular imaging with US. Notably, these FA-NDs can be triggered by low-intensity focused US (LIFU) sonication, providing excellent US enhancement in B-mode and contrast-enhanced US mode in vitro. After intravenous administration into nude mice bearing SKOV3 ovarian carcinomas, 1,1'-dioctadecyl-3,3,3',3' -tetramethylindotricarbocyanine iodide-labeled FA-NDs were found to accumulate in the tumor region. FA-NDs injection followed by LIFU sonication exhibited remarkable US contrast enhancement in the tumor region. In conclusion, combining our elaborately developed FA-NDs with LIFU sonication provides a potential protocol for US molecular imaging in folate receptor-overexpressing tumors. Keywords: low-intensity focused ultrasound, perfluoropentane nanodroplets, acoustic droplet vaporization, ultrasound molecular imaging, targeting